Evergreens : celebrating six decades on Columbia Records [compact disc] - Streisand, Barbra; Streisand, Barbra (Legacy, 2023)
The album commemorates the unparalleled career of a once-in-a-lifetime artist, who has literally conquered every entertainment medium, the night club stage, the concert stage, the Broadway stage, the big screen, the small screen, and course, the recording studio. The songs chosen have nothing to do with statistics or certifications. Instead, they were hand-selected by Barbra and exemplify her emotional connection to these melodies and lyrics, each holding a special place in her heart and memory. The album features 22 songs, one song from every studio album she has released. The songs were hand selected by Barbra as some of her favorite songs throughout her career, many are deep tracks. None of these tracks have appeared on previous Streisand compilation albums before.